Continuous IPPP links for UTC. (1st August 2022) - Petit, G; Meynadier, F; Harmegnies, A; Parra, C
Abstract: The technique of precise point positioning with integer ambiguity resolution (IPPP) has been developed for many years and has been shown to significantly improve the long-term performance of time and frequency transfer with respect to other GNSS-based techniques. In this paper, we present results of GPS IPPP links over a period of 22 months for a dozen time laboratories participating to UTC. We show that continuous links, in which the continuity of the GPS phase measurements is preserved, can be maintained for periods exceeding one year and further extended if data from two receivers per station are available. We quantify the frequency transfer uncertainty of IPPP by comparison to optical links and show how IPPP could improve UTC links to below 1 × 10 −16 relative frequency uncertainty over averaging times of up to one month, i.e. the characteristic period of UTC publication. Comparisons of primary and secondary frequency standards reported for TAI indicate that IPPP could somewhat improve the accuracy of TAI/UTC. Comparisons of IPPP to two-way time transfer techniques reveal very long-term ns-size instabilities which must be further studied. Use of IPPP for UTC links is possible only if integer GNSS satellite products become available with a short delay and we report on such experimental products. Finally, we discuss the practical implications of using IPPP link in UTC and describe how the necessary steps could be implemented.